2020
DOI: 10.3390/w12072052
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Prediction Modeling Studies of Organic Pollutants Removal from Municipal Wastewater using Moringa oleifera Biomass as a Coagulant

Abstract: This study investigated the potential of Moringa oleifera (MO) seed biomass as a coagulant for the removal of turbidity, biochemical oxygen demand (BOD), and chemical oxygen demand (COD) of municipal wastewater. Triplicated laboratory experiments using MO coagulant added at varying treatment dosages of 50, 100, 150, 200 mg/L, and a control (0 mg/L) treatment were performed for a settling period of 250 min at room temperature. Kinetics and prediction variables of cumulative turbidity, BOD, and COD removal were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 40 publications
0
22
1
1
Order By: Relevance
“…Furthermore, the plateau of R-values revealed the degree of particle aggregation with respect to time taken for floc breakage to occur. The presence of floc breakage and the results obtained confirm that incorporation of the F increased the molecular weight of the coagulant components [ 50 , 52 ].…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Furthermore, the plateau of R-values revealed the degree of particle aggregation with respect to time taken for floc breakage to occur. The presence of floc breakage and the results obtained confirm that incorporation of the F increased the molecular weight of the coagulant components [ 50 , 52 ].…”
Section: Resultsmentioning
confidence: 74%
“…The data obtained was fitted to kinetics Equations (7) and (9) to evaluate the performance for the treatment of the contaminants. The pollutant removal rate in a reaction-based system depends on numerous internal and external factors such as temperature, dosage, and the characteristics of wastewater itself [ 52 ]. When the reaction proceeds, pollutant particles attach themselves to both chemical and physical binding sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was, however, no significant influence in other physicochemical parameters including the pH. Adelodun et al [49] also found that there was no significant difference in turbidity removal for MO dosage 150mg/L and 200mg/L. The result from a study on municipal effluent treatment using seed of MO depicted that turbidity removal reached a maximum of 94.44% with 15% MO biomass, this decreased marginally to 94.42% when the concentration was raised to 20%.…”
Section: Physicochemical Properties Of Effluent Samplesmentioning
confidence: 96%
“…The ability of Moringa oleifera (MO) seeds as a coagulant to remove turbidity, biochemical oxygen demand (BOD), and chemical oxygen demand (COD) from urban wastewater was investigated by Adelodun et al [5]. Their outcomes indicated that employing a MO dose of 150 mg/L, the maximal reduction in turbidity, BOD, and COD was 94%, 69%, and 58%, respectively.…”
mentioning
confidence: 99%